Atrial flutter – clinical risk factors and adverse outcomes in the Framingham Heart Study - Rahman, Faisal (Heart Rhythm, 2015)
BACKGROUND: Few epidemiological cohort studies have evaluated atrial flutter (flutter) as an arrhythmia distinct from atrial fibrillation (AF). OBJECTIVE: To examine the clinical correlates of flutter and its associated outcomes to distinguish them from those associated with AF in the Framingham Heart Study. METHODS: We reviewed and adjudicated electrocardiograms previously classified as flutter or AF/flutter and another 100 electrocardiograms randomly selected from AF cases. We examined the clinical correlates of flutter by matching up to 5 AF and 5 referents to each flutter case using a nested case-referent design. We determined the 10-year outcomes associated with flutter with Cox models. RESULTS: During mean follow-up of 33.0±12.2 years, 112 participants (mean age 72±10 years, 30% women) developed flutter. In multivariable analyses, smoking (odds ratio [OR] 2.84; 95% confidence interval [CI], 1.54 to 5.23), increased PR interval (OR 1.28 per SD; 95% CI, 1.03 to 1.60), myocardial infarction (OR 2.25; 95% CI, 1.05 to 4.80) and heart failure (OR 5.22; 95% CI, 1.26 to 21.64) were associated with incident flutter. In age- and sex-adjusted models, flutter (vs. referents) was associated with 10-year increased risk of AF (hazard ratio [HR] 5.01; 95% CI, 3.14 to 7.99), myocardial infarction (HR 3.05; 95% CI, 1.42 to 6.59), heart failure (HR 4.14; 95% CI, 1.90 to 8.99), stroke (HR 2.17; 95% CI, 1.13 to 4.17), and mortality (HR 2.00; 95% CI, 1.44 to 2.79). CONCLUSIONS: We identified the clinical correlates associated with flutter and observed that flutter was associated with multiple adverse outcomes.